2008
DOI: 10.1128/jcm.00167-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Babesia sp. from a Sable Antelope ( Hippotragus niger Harris, 1838)

Abstract: Babesiosis in a sable antelope (Hippotragus niger Harris, 1838) was first reported in 1930; the parasite was named Babesia irvinesmithi. Recently, specimens from an adult sable that presented with a sudden onset of disease and that subsequently died during immobilization were submitted for molecular characterization. Microscopic examination of thin blood smears revealed the presence of small piroplasms. DNA was extracted from blood samples; the V4 variable region of the 18S rRNA gene was amplified and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 26 publications
1
79
0
Order By: Relevance
“…The reverse line blot (RLB) method (Gubbels et al 1999), based on simultaneous detection of the 18S rRNA gene for various Babesia and Theileria species, has been extensively used for surveillance purposes (Georges et al 2001; Almerìa et al 2002;Oura et al 2004;Nijhof et al 2003Nijhof et al , 2005Altay et al 2007;M'ghirbi et al 2008;Altay et al 2008;Matjila et al 2008;Oosthuizen et al 2008; Almerìa et al 2009;Salih et al 2010;Yusufmia et al 2010; Tomassone et al 2012;Ceci et al 2014;Githaka et al 2014;Eygelaar et al 2015;Njiiri et al 2015). The method relies on the amplification of the V4 hypervariable region of the 18S rRNA gene, followed by hybridization to probes for various The current study aimed to assess whether other genotypes may be amplified by the primers used in these assays, since it was shown that multiple templates may affect sensitivity of the diagnostic assays (Pienaar et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…The reverse line blot (RLB) method (Gubbels et al 1999), based on simultaneous detection of the 18S rRNA gene for various Babesia and Theileria species, has been extensively used for surveillance purposes (Georges et al 2001; Almerìa et al 2002;Oura et al 2004;Nijhof et al 2003Nijhof et al , 2005Altay et al 2007;M'ghirbi et al 2008;Altay et al 2008;Matjila et al 2008;Oosthuizen et al 2008; Almerìa et al 2009;Salih et al 2010;Yusufmia et al 2010; Tomassone et al 2012;Ceci et al 2014;Githaka et al 2014;Eygelaar et al 2015;Njiiri et al 2015). The method relies on the amplification of the V4 hypervariable region of the 18S rRNA gene, followed by hybridization to probes for various The current study aimed to assess whether other genotypes may be amplified by the primers used in these assays, since it was shown that multiple templates may affect sensitivity of the diagnostic assays (Pienaar et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Babesia sp. (sable) was identified in a sable antelope that died from an unknown illness on a game ranch in the Limpopo province, South Africa (Oosthuizen et al, 2008). While the parasite was observed in blood smears, there was no direct evidence that it was the cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…(sable) (Nijhof et al, 2005), Babesia sp. (sable) (Oosthuizen et al, 2008), and B. bicornis (Nijhof et al, 2003) were included on the membrane (Table 2). Table 2.…”
Section: Reverse Line Blot (Rlb) Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…High seroprevalence of Anaplasma species, ranging from 75 to 100%, was found in wildlife at the livestock-wildlife interface in Kenya (Ngeranwa et al 2008). Species examined were eland, blue wildebeest, kongoni (Damaliscus (Nijhof et al 2003;Nijhof et al 2005;Oosthuizen et al 2008;Oosthuizen et al 2009). …”
Section: Anaplasma Marginalementioning
confidence: 99%